A battery, an electric device
Patent Information
- Application Number
- CN202611240196.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-30
AI Technical Summary
然而,上述方法在提升压实密度的同时,正极材料的吸水性问题在高温或高湿环境下会变得尤为突出,而正极材料吸水后会引发电解液分解、产气加剧,进而导致电池循环寿命缩短及安全隐患增加
[0038]本申请所提供的电池,通过超小颗粒占比f、峰谷强度m与峰强a、b的比值n的动态平衡,以及电解液中腈类化合物含量d的控制,能够在提升能量密度的同时抑制超小颗粒带来的吸水倾向及由此引发的与锂盐副反应,进而降低产气和寿命衰减风险,并兼顾电池的离子传输与动力学性能。
Smart Images

Figure CN123018060A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of energy storage technology, specifically to a battery and an electrical device. Background Technology
[0002] Lithium iron phosphate (LFP) batteries are widely used in new energy vehicles, energy storage systems, power tools, and consumer electronics due to their excellent thermal stability, cycle life, and safety. However, as users' demands for battery energy density and cycle performance increase, the performance bottlenecks of LFP batteries are gradually becoming apparent.
[0003] In existing technologies, a multi-level particle blending strategy is typically employed to improve the compaction density of cathode materials in lithium iron phosphate batteries. This involves mixing particles of different sizes to achieve gap filling and space optimization. However, while this method increases compaction density, the water absorption of the cathode material becomes particularly pronounced under high temperature or high humidity environments. Water absorption by the cathode material can trigger electrolyte decomposition and increased gas production, leading to a shortened battery cycle life and increased safety hazards.
[0004] Therefore, it is of great significance to find a way to increase the compaction density of cathode materials while effectively suppressing their water absorption, thereby obtaining batteries with high energy density and high safety performance. Summary of the Invention
[0005] The battery and electrical equipment provided in this application have the advantages of high energy density and low risk of gas production, and excellent ion transport performance.
[0006] In a first aspect, embodiments of this application provide a battery, including a positive electrode sheet and an electrolyte. The positive electrode sheet includes a positive electrode material, which includes lithium iron phosphate. The lithium iron phosphate includes ultra-small particles, small particles, and large particles. The particle size range of the ultra-small particles is 20nm-100nm. Based on the total number of lithium iron phosphate particles, the proportion of the number of ultra-small particles is f.
[0007] The volumetric particle size distribution curve of the cathode material includes a first peak corresponding to the ultrasmall particles, a second peak corresponding to the small particles, and a third peak corresponding to the large particles.
[0008] In the first peak, the particle size A corresponding to the peak value is 30nm-90nm, and the peak intensity corresponding to the peak value is a;
[0009] In the second peak, the particle size B corresponding to the peak value is 120nm-800nm, and the peak intensity corresponding to the peak value is b.
[0010] The peak intensity corresponding to the valley between the first and second peaks is m;
[0011] In the third peak, the particle size C corresponding to the peak value is 1μm-4μm;
[0012] The electrolyte contains nitrile compounds, and the mass content of the nitrile compounds is d based on the total mass of the electrolyte;
[0013] f, m, and b satisfy: 0.35 ≤ f / (n×d) ≤ 103;
[0014] Where n = m / (a + b).
[0015] In one specific implementation, 1.5 ≤ f / (n×d) ≤ 17.
[0016] In one specific implementation, 5% ≤ f ≤ 20%.
[0017] In one specific implementation, 5% ≤ d ≤ 50%.
[0018] In one specific implementation, 0.0357 ≤ n ≤ 0.333.
[0019] In one specific implementation, 0.5% < a ≤ 6%.
[0020] In one specific implementation, the particle size M corresponding to m satisfies: 100nm≤M≤120nm.
[0021] In one specific implementation, the particle size A corresponding to a satisfies: 20nm≤|MA|≤80nm.
[0022] In one specific implementation, in the second peak, the particle size corresponding to the peak value b is B, where 100nm≤|BM|≤700nm.
[0023] In one specific implementation, 4% ≤ b ≤ 10%.
[0024] In one specific implementation, 0.5% ≤ m ≤ 2%.
[0025] In one specific implementation, the peak intensity corresponding to the peak value of the third peak is c, and the peak intensity c corresponding to the peak value satisfies: 4%≤c≤10%.
[0026] In one specific implementation, the peak intensity corresponding to the valley between the second peak and the third peak is q, where 0.1≤q / (b+c)≤0.5.
[0027] In one specific implementation, the particle size Q corresponding to q satisfies: 0.2μm≤Q≤1.0μm.
[0028] In one specific implementation, the peak intensity q satisfies: 2%≤q≤8%.
[0029] In one specific embodiment, the particle size distribution curve also includes a fourth peak corresponding to the ultra-large particles, wherein the particle size D corresponding to the peak value of the fourth peak satisfies: 7μm<C≤25μm.
[0030] In one specific implementation, the particle size range of the ultra-large particles is 4μm-35μm.
[0031] In one specific embodiment, the nitrile compound includes at least one selected from acetonitrile, propionitrile, succinic anionitrile, glutaronitrile, adiponitrile, benzonitrile, phthalonitrile, and 1,3,6-hexanetrionitrile.
[0032] In one specific embodiment, the nitrile compound includes at least one selected from acetonitrile, butadionitrile, and 1,3,6-hexanetrionitrile.
[0033] In one specific embodiment, the lithium iron phosphate surface further includes a carbon coating layer; preferably, the thickness of the carbon coating layer is 0.5 nm-120 nm.
[0034] In one specific embodiment, the specific surface area of the positive electrode material is 5 m². 2 / g -40 m 2 / g; and / or, the porosity of the positive electrode is 10%-40%.
[0035] In one specific embodiment, the battery further includes a negative electrode sheet, wherein the negative electrode active layer of the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes at least one of graphite and silicon-based materials.
[0036] In one specific embodiment, the positive electrode sheet includes a positive current collector and a positive active layer disposed on opposite sides of the positive current collector, with the positive electrode material located in the positive active layer.
[0037] Secondly, embodiments of this application also provide an electrical device, including the battery described above.
[0038] The battery provided in this application, through the dynamic balance of the proportion of ultra-small particles f, the ratio of peak-valley intensity m to peak intensity a, b, and n, and the control of the content of nitrile compounds d in the electrolyte, can improve energy density while suppressing the water absorption tendency caused by ultra-small particles and the resulting side reaction with lithium salt, thereby reducing the risk of gas generation and lifespan degradation, and taking into account the ion transport and kinetic performance of the battery. Attached Figure Description
[0039] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0040] Figure 1A volumetric particle size distribution curve provided for this application. Detailed Implementation
[0041] To enable those skilled in the art to better understand the solutions of this application, a further detailed description of this application is provided below. The specific embodiments listed below are merely descriptions of the principles and features of this application; the examples are only for explaining this application and are not intended to limit its scope. Other embodiments obtained by those skilled in the art based on the embodiments of this application without inventive effort are all within the scope of protection of this application.
[0042] To address the issue that existing technologies often result in limited increases in compaction density when using simple particle blending to improve lithium iron phosphate (LFP) compaction density, the applicant's research has found that adding ultra-small particles can further increase compaction density, but this increases the water absorption capacity of the cathode material. When the cathode material absorbs water, the moisture reacts with lithium salts (such as LiPF6) in the electrolyte, leading to a series of irreversible side reactions and increased gas production. This can directly cause an increase in internal battery pressure, leading to battery swelling. Simultaneously, the generated HF further corrodes the coating layer (such as LiPO3 and Al2O3) on the cathode material surface, compromising the structural stability of the cathode and accelerating the dissolution of active materials. Studies have shown that even if the cathode material absorbs only trace amounts of moisture, it can rapidly trigger the above reactions after electrolyte injection, causing a doubling of gas production during battery formation, accelerated capacity decay during cycling, and a shortened lifespan.
[0043] In response to the above problems, the applicant believes that the following reasons may be the main factors that lead to the increase in water absorption capacity of the cathode material by adding ultra-small particles: (1) When the lithium iron phosphate particles are reduced from micron to nano, the particle size shrinks and the specific surface area increases accordingly. The significant increase in specific surface area means that the number of surface atoms exposed to the air increases sharply. For lithium iron phosphate, there are a large number of unsaturated chemical bonds on the surface atoms (such as Fe-O bonds and dangling bonds of PO bonds). These unsaturated bonds will make the surface atoms in a high-energy unstable state, and they have a strong tendency to adsorb surrounding polar molecules (such as H2O) to reduce the surface energy. (2) The surface lattice arrangement of nanoparticles is irregular, and defects such as vacancies and dislocations are easily formed. These defects are the preferred sites for water molecule adsorption. At the same time, the atomic coordination environment at the defects is abnormal, which will produce local charge imbalance and also adsorb polar water molecules through electrostatic interaction. (3) The unsaturated bonds on the surface of lithium iron phosphate are also easy to react with trace amounts of moisture in the air to generate hydrophilic groups such as hydroxyl (-OH). Ultra-small particles have a large specific surface area and a much higher density of hydroxyl groups than micron-sized particles. Hydrogen bonds can be formed between hydroxyl groups and water molecules, further enhancing the adsorption capacity for water molecules and forming a positive feedback loop of "adsorption-reaction-re-adsorption". (4) Ultra-small particles are prone to forming loose aggregates. A large number of nano-sized pores will be generated inside the aggregates. The pore size of these nano-pores is comparable to the diameter of water molecules (about 0.28 nm), which will generate strong capillary action. The curvature of the liquid surface inside the pores is extremely small. According to the Yang-Laplace equation, a negative pressure much greater than the external atmospheric pressure will be formed inside the pores, thereby "drawing" water molecules in the air into the pores and adsorbing them firmly.
[0044] Further research has shown that adding nitrile compounds to the electrolyte can improve water absorption. Specifically, nitrile compounds can reduce the adsorption capacity of the cathode material for water through a dual effect of surface coating barrier and chemical complexation capture. However, the addition of nitrile compounds increases electrolyte viscosity, hindering lithium-ion transport and thus degrading battery kinetic performance.
[0045] Based on this, this application provides a battery including a positive electrode sheet and an electrolyte. The positive electrode sheet includes a positive electrode material, which includes lithium iron phosphate. The lithium iron phosphate includes ultra-small particles, small particles, and large particles. The particle size range of the ultra-small particles is 20nm-100nm. Based on the total number of lithium iron phosphate particles, the proportion of ultra-small particles is f.
[0046] The volume particle size distribution curve of the cathode material includes a first peak corresponding to ultrasmall particles, a second peak corresponding to small particles, and a third peak corresponding to large particles;
[0047] In the first peak, the particle size A corresponding to the peak value is 30nm-90nm, and the peak intensity corresponding to the peak value is a;
[0048] In the second peak, the particle size B corresponding to the peak value is 120nm-800nm, and the peak intensity corresponding to the peak value is b.
[0049] The peak intensity corresponding to the valley between the first and second peaks is m;
[0050] In the third peak, the particle size C corresponding to the peak value is 1μm-4μm;
[0051] The electrolyte contains nitrile compounds, and the mass content of nitrile compounds is d based on the total mass of the electrolyte;
[0052] f, m, and b satisfy: 0.35 ≤ f / (n×d) ≤ 103;
[0053] Where n = m / (a + b).
[0054] In this application, the lithium iron phosphate material is categorized into ultra-small particles, large particles, and large particles based on the particle size distribution curve's horizontal axis. The particle size relationship satisfies the following: large particle size > small particle size > ultra-small particle size. The first and second peaks are continuous, meaning the end of the first peak is the starting point of the second peak.
[0055] This application achieves a balance between the multi-level particle packing effect and the interfacial water absorption suppression capability by synergistically constraining the particle size distribution and electrolyte additive content. This improves the problem of increased water absorption and compaction density in lithium iron phosphate batteries caused by the introduction of ultra-small particles, while also considering the battery's kinetic performance. Specifically, through the dynamic balance of the proportion of ultra-small particles (f), the peak-valley intensity (m), and the ratio (n) of peak intensities (a, b), and the control of the nitrile compound content (d) in the electrolyte, the synergistic control of the cathode material's compaction density, water absorption risk, and battery kinetic performance is achieved.
[0056] Specifically, n is the normalized peak-valley intensity characterization value, reflecting the proportion of intermediate-sized particles between small and large particles relative to the overall intensity of the bimodal peaks, and is used to regulate compaction density and ion transport performance; the proportion of ultra-small particles f regulates the ability of ultra-small particles to fill the gaps (i.e., compaction density), gas generation, and ion transport performance; the content of nitrile compounds in the electrolyte d regulates gas generation and ion transport performance. Through the synergistic effect of the above three factors, compaction density, water absorption risk, and battery kinetic performance are all taken into account.
[0057] It should be noted that the volumetric particle size distribution curve is the particle size distribution data of lithium iron phosphate particles, used to characterize the contribution of particles of different sizes in the material to the overall volume distribution. The peak value refers to the signal intensity (i.e., peak intensity) presented at the peak apex. The particle size corresponding to the peak value refers to the particle size value corresponding to the peak apex (i.e., the highest point of the peak). The valley refers to the region with relatively low intensity in the spectrum. The peak intensity corresponding to the valley refers to the signal intensity presented in the region with low intensity.
[0058] Figure 1 The volumetric particle size distribution curve of a lithium iron phosphate material provided in this application includes a first peak representing the particle size of ultrasmall particles and a second peak representing the particle size of small particles. The peak intensity corresponding to the apex of the first peak (i.e., the peak value of the first peak) is denoted as 'a', the peak intensity corresponding to the apex of the second peak (i.e., the peak value of the second peak) is denoted as 'b', and the peak intensity corresponding to the valley between the first and second peaks is denoted as 'm'. The particle size corresponding to the apex of the particle size peak characterizes the core bulk size of the corresponding particle size, that is, the particle with this size has the highest volume contribution within this type of particle. For example, the core bulk size of the ultrasmall particles is 'A', and the core bulk size of the small particles is 'B'.
[0059] In this application, A can be 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, or any value between any two of the above. B can be 120nm, 150nm, 180nm, 200nm, 250nm, 300nm, 350nm, 400nm, 500nm, 600nm, 700nm, 800nm, or any value between any two of the above. C can be 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, or any value between any two of the above.
[0060] f represents the percentage of ultra-small particles. Due to their large specific surface area and high surface energy, ultra-small particles readily absorb moisture from the air. Furthermore, the secondary particle aggregates they form contain numerous mesopores / micropores, further trapping moisture. After absorbing moisture, the water reacts with lithium salts (such as LiPF6) in the electrolyte to generate corrosive gases (such as HF and POF3) and byproducts (such as LiF), leading to increased internal battery pressure, deterioration of the cathode material structure, and decreased cycle performance. A large f value indicates a high proportion of ultra-small particles, which helps improve energy density but increases the water absorption of the cathode material and the amount of gas generated inside the battery. A small f value results in minimal improvement in compaction density, which is detrimental to increasing battery energy density.
[0061] f can be adjusted by controlling the mass ratio of ultra-small particles; the more ultra-small particles there are, the larger f becomes.
[0062] The volumetric particle size distribution curve of the cathode material exhibits a first peak, a second peak, and a third peak. The first peak corresponds to ultrasmall particles, the second peak to small particles, and the third peak to large particles. Large and small particles primarily provide the main structural framework and active material loading, while ultrasmall particles are embedded in the gaps between these frameworks to achieve tight filling. A valley exists between the first and second peaks, reflecting the contribution (i.e., relative content) of intermediate-sized particles to the total volume. An excessive number of intermediate-sized particles simultaneously weakens the micro-filling effect of ultrasmall particles and the framework support effect of small particles, making the bimodal structure less distinct and hindering the formation of an ideal pore gradient between particles.
[0063] In this application, the peak value of the first peak is denoted as 'a', the peak value of the second peak is denoted as 'b', the peak intensity of the valley between the first and second peaks is denoted as 'm', and 'n' is defined as 'm / (a+b)'. Here, 'a' and 'b' can be understood as the peak intensities at corresponding peak positions on the volumetric particle size distribution curve, representing the significance of ultra-small particle groups and small particle groups in the overall distribution; 'm' represents the valley intensity of the intermediate-sized particle region between the two peaks; and 'n' is the normalized valley intensity value, used to reflect the proportion of intermediate-sized particles relative to the overall intensity of the two peaks. By using 'n' instead of just 'm', the influence of variations in absolute peak height between different batches on the result determination can be weakened, making the particle size distribution evaluation more comparable and stable.
[0064] Specifically, when n is low, it indicates that the valley between the two peaks is deep, the content of intermediate-sized particles is relatively low, the bimodal distribution is clearer, and the filling synergy between ultra-small particles and small particles is more sufficient; when n is high, it indicates that the relative content of intermediate-sized particles increases, the bimodal separation decreases, and the particle system tends to be continuously distributed, thereby weakening the multi-level packing advantage.
[0065] It should be noted that the sizes of a, b, m, and n can be adjusted by regulating the distribution of ultrafine and fine particles. Specifically, by increasing the grinding intensity, the particle size distribution range can be reduced, thus increasing the peak values of a and b. For example, a higher classification frequency results in a narrower particle distribution and larger peak values of a and b. Conversely, increasing the classification frequency can reduce the particle size distribution range, increasing peak values of a and b, and decreasing m and n. Furthermore, the peak values of each peak can be controlled by adjusting the proportions of different particles. For instance, more first particles result in a higher peak value, and more second particles result in a higher peak value. Peak particle sizes A and B can be increased by increasing the sintering temperature. For example, when the sintering temperature is 760℃-820℃ and sintering time is 10-12 hours, the peak particle size of the second peak is greater than that when the sintering temperature is 700℃-760℃ and sintering time is 6-10 hours. However, this is not the only method; those skilled in the art can achieve this through other means.
[0066] The electrolyte contains nitrile compounds, with a mass content of nitrile compounds denoted as 'd', meaning the mass percentage of nitrile compounds based on the total mass of the electrolyte. These nitrile compounds contain polar cyano groups, which can form a dense coating layer on the surface of the cathode material, preventing direct contact between water and the material, reducing water absorption channels. Furthermore, the cyano groups can undergo complexation reactions with hydrogen molecules on the surface of the cathode material or in adsorbed water molecules, "fixing" the water molecules within the complex and hindering their free reaction. This synergistic effect effectively reduces the water absorption of the cathode material. However, excessive nitrile compounds increase the viscosity of the electrolyte, increase lithium-ion transport impedance, and degrade battery kinetic performance. Therefore, this application does not simply pursue high addition levels to suppress water absorption, but rather links 'd' with the f and n of the particle system to balance interfacial stability and ion transport.
[0067] It should be noted that the mass content d of nitrile compounds in this application can be obtained directly from the ingredients or detected by the following methods:
[0068] Use a battery charging and discharging device to discharge the secondary battery under test to the lower limit voltage. After recording the battery number / barcode, disassemble the battery in a glove box (H2O≤0.1ppm, O2≤0.1ppm) to collect the electrolyte. There are three methods for collecting the electrolyte: After opening the battery cover, (1) if there is free electrolyte, use a pipette to collect the electrolyte into a 5mL sample tube and seal it with sealing glue to prevent electrolyte leakage; (2) if there is no free electrolyte, a hydraulic press (such as Beijing Hengao) can be used. (3) Add an appropriate amount of ethyl acetate extractant to the battery and record the ethyl acetate content. After adding ethyl acetate, put the battery into an aluminum-plastic bag and seal it with a heat sealer. Transfer it to an ultrasonic oscillator and oscillate for 12 hours to allow the electrolyte in the electrode to mix fully with ethyl acetate. Then, use a pipette to draw the mixture of ethyl acetate and electrolyte into a 5 mL sample tube and seal the sample tube with sealing glue.
[0069] The collected electrolyte samples were injected into an Agilent Intuvo 9000 gas chromatograph-mass spectrometer using a microsyringe to obtain GC-MS spectra. The electrolyte was dissolved in EMC solvent to prepare solutions of different concentrations, and these solutions were injected into the Agilent Intuvo 9000 gas chromatograph-mass spectrometer to obtain standard GC-MS spectra. The GC-MS spectra of the electrolyte to be tested were compared with the standard GC-MS spectra to confirm the presence of the corresponding nitrile components. The test solutions were then injected into the GC. The content of the nitrile components, d, was determined based on the ratio of the peak area S1 of the nitrile components in the test electrolyte to the peak area S2 of the standard solution, and the concentration C1 in the standard solution: d = S1 / S2 × C1.
[0070] The core of this application's embodiments lies in ensuring that f, n, and d satisfy 0.35 ≤ f / (n×d) ≤ 103, where n = m / (a+b). For example, f / (n×d) can be 0.35, 1, 10, 20, 30, 50, 70, 90, 103, or any value between any two of the above. In this formula, f reflects the proportion of ultra-small particles, representing the filling capacity; n reflects the proportion of intermediate-sized particles, representing the clarity of the bimodal distribution and the synergy of particle packing; and d reflects the intensity of the addition of nitrile compounds in the electrolyte, representing the interfacial water absorption suppression and regulation capability. By unifying the particle structure parameters and electrolyte formulation parameters under the same criterion through the formula f / (n×d), the filling requirements of ultra-small particles, the degree of interference from intermediate-sized particles, and the matching between interfacial water suppressants can be comprehensively evaluated.
[0071] If the ratio is below 0.35, it means that n and / or d are relatively large, or f is small. In this case, there are too many intermediate-sized particles or excessive addition of nitrile compounds. The former will weaken the bimodal synergistic packing effect, and the latter will increase electrolyte viscosity and hinder ion migration. Even if side reactions are suppressed, it is difficult to balance compaction density and kinetic performance. If the ratio is above 103, it usually means that f is too large and n and d are insufficient. Although the filling tendency of ultra-small particles is enhanced, the corresponding interfacial protection and water absorption inhibition capacity are insufficient. It is easy to produce increased gas production, capacity decay and cycle deterioration due to the moisture absorption and side reactions caused by high specific surface area. By controlling the ratio within the range of 0.35-103, a quantitative matching relationship is formed between particle packing and interfacial chemistry, so that the positive filling effect of ultra-small particles can be released, while its potential side effects are offset by an appropriate amount of nitrile compounds and a low proportion of intermediate-sized particles, thereby achieving a comprehensive balance between compaction density, gas production control and rate performance.
[0072] In one specific implementation, 1.5 ≤ f / (n×d) ≤ 17.
[0073] Studies have shown that when 1.5≤f / (n×d)≤17, it is beneficial to better balance compaction density, gas production control and rate performance.
[0074] In one specific implementation, 5% ≤ f ≤ 20%. Specifically, the value of f can be 5%, 10%, 15%, 20%, or any value between any two of the above.
[0075] f is used to characterize the proportion of ultra-small particles in lithium iron phosphate. By limiting f to 5% to 20%, ultra-small particles of 20nm-100nm can fully fill the pores between small particles, improve the compactness of particle packing, and avoid significantly increasing the specific surface area due to excessive refinement, thus avoiding enhanced water absorption and aggravated interfacial side reactions. Preferably, f can be 8%-12% to obtain a more stable compaction density improvement effect.
[0076] In one specific implementation, 5% ≤ d ≤ 50%. Specifically, the value of d can be 5%, 10%, 15%, 20%, 30%, 40%, 50%, or any value between any two of the above values.
[0077] d represents the content of nitrile compounds in the electrolyte. Controlling the content of nitrile compounds to 5%-50%, preferably 10%-30%, can ensure good ion transport performance while maintaining good water absorption inhibition.
[0078] In one specific implementation, 0.0357 ≤ n ≤ 0.333. Specifically, n can be 0.0357, 0.04, 0.06, 0.08, 0.1, 0.2, 0.3, 0.333, or any value between any two of the above.
[0079] n is the ratio of the intensity of the valley between the particle size peaks of ultra-small particles and small particles to the peak values of ultra-small particles and small particles. It represents the relative content of intermediate particles between small and ultra-small particles. 0.0357≤n≤0.333 indicates that a moderate valley depth is still maintained between the first peak and the second peak, that is, the proportion of intermediate particle size particles is controlled within a range that does not weaken the synergistic filling effect of multi-level particles. When n is 0.075-0.20, the filling effect is better.
[0080] By adjusting the pulverization and classification, airflow pulverization pressure, and raw material ratio, n can be kept within this range. This reduces the interference of intermediate-sized particles on the interstitial filling effect of ultra-small particles and allows the ultra-small particles corresponding to the first peak and the small particles corresponding to the second peak to form a more reasonable gradation structure. Preferably, n is taken as 0.075-0.20 to better balance the requirements of densification and water absorption inhibition.
[0081] In one specific implementation, 0.5% < a ≤ 6%. Specifically, a can be 0.6%, 1%, 2%, 3%, 4%, 5%, 6%, or any value between any two of the above.
[0082] 'a' is the peak height of the first peak in the particle size distribution curve of the cathode material. Limiting 'a' to between 0.5% and 4% ensures that ultra-small particles maintain a identifiable but not excessively concentrated proportion within the overall lithium iron phosphate particle system. This fills the pores between large and small particles while avoiding a sharp increase in specific surface area, an increase in water absorption sites, and a decrease in slurry processability caused by an excessive number of ultra-small particles. Preferably, 'a' can be controlled within the range of 1%-2% to more stably balance particle packing and interfacial stability.
[0083] In one specific embodiment, the particle size M corresponding to m satisfies: 100nm ≤ M ≤ 120nm. Specifically, M can be 100nm, 105nm, 110nm, 115nm, 120nm, or any value between any two of the above values.
[0084] By controlling the particle size M corresponding to the peak and valley within 100nm-120nm, the intermediate particle size particles located between ultra-small particles and small particles can be kept at a relatively controlled level, without significantly affecting the synergistic filling effect of ultra-small particles and small particles.
[0085] Furthermore, the particle size A corresponding to 'a' satisfies: 20nm ≤ |MA| ≤ 80nm, that is, the difference between the particle size m corresponding to the valley of the first peak and the particle size A corresponding to the peak value of the first peak is 20nm-80nm. Specifically, |MA| can be 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, or any value between any two of the above values.
[0086] By controlling the difference between the peak-valley particle size M and the first peak-to-peak particle size A, the span between ultra-small particles and the intermediate particle size corresponding to the peak-valley can be controlled within a moderate range. This ensures that the ultra-small particles can effectively fill the pores between small particles and intermediate particle size particles, without causing excessive breakage of the particle gradation due to excessive particle size span, thus facilitating the formation of a more continuous and compact packing structure.
[0087] Furthermore, in the second peak, the particle size corresponding to the peak value is B, where 100nm ≤ |BM| ≤ 700nm. That is, the difference between the particle size m corresponding to the valley of the first and second peaks and the particle size B corresponding to the peak value of the second peak is 100nm-700nm. Specifically, |BM| can be 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, or any value between any two of the above.
[0088] By controlling the difference between the peak-valley particle size M and the second peak-to-peak particle size B within the aforementioned range, sufficient particle size spacing is maintained between the second peak-to-peak and the valley, allowing for a clear hierarchical distribution between small and ultra-small particles. This avoids particle sizes being too similar, resulting in indistinct packing layers. The peak-valley particle size M typically reflects the lowest point of the transition zone between the two types of particles. By controlling the difference between B and M, the particles corresponding to the second peak can form stable support within the filling skeleton, while the ultra-small particles corresponding to the first peak can more easily embed into the larger particle gaps, thereby improving the overall packing density.
[0089] In one specific implementation, 4% ≤ b ≤ 10%, meaning the peak intensity of the second peak value b is 4%-10%. Specifically, b can be 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any value between any two of the above. Controlling b between 4%-10%, preferably 6%-8%, allows the small particles to form sufficiently obvious main distribution characteristics and, together with the ultra-small particles, construct a multi-level filling structure, thereby improving the compactness of particle packing.
[0090] In one specific implementation, 0.5% ≤ m ≤ 2%, meaning the peak intensity m of the valley between the first and second peaks is 0.5%-2%. Specifically, m can be 0.5%, 1%, 1.5%, 2%, or any value between any two of these. Controlling m within this range can suppress the problem of pores being difficult to compress due to an excessive number of intermediate-sized particles, while avoiding excessive weakening of the continuous transition of particle size distribution, thereby ensuring the filling effect. The effect is even better when the valley intensity m is 0.75-1.5%.
[0091] Furthermore, the peak intensity corresponding to the peak value of the third peak is c, and the peak intensity c corresponding to the peak value satisfies: 4%≤c≤10%. Specifically, c can be 4%, 6%, 8%, 10%, or any value between any two of the above values.
[0092] Controlling the peak intensity c corresponding to the peak value of the third peak to 4%-10% helps ensure a reasonable relative content of large particles, avoiding excessive content that leads to a decrease in coating uniformity and insufficient content that makes it difficult to form effective gradation filling.
[0093] Furthermore, the peak intensity corresponding to the valley between the second and third peaks is q, where 0.1 ≤ q / (b+c) ≤ 0.5. Specifically, q / (b+c) can be 0.1, 0.2, 0.3, 0.4, 0.5, or any value between any two of the above.
[0094] In this formula, q represents the intensity of the valley value corresponding to the intermediate particle size between the second and third peaks, b is the peak value of the second peak, and c is the peak value of the third peak. 0.1 ≤ q / (b+c) ≤ 0.5 indicates that the valley intensity is within a moderate range relative to the average level of the peaks on both sides. By controlling q within this range, a certain amount of transitional particle size particles can be retained between the second and third peaks, maintaining the continuity of particle size distribution and the stability of the compound, while avoiding excessively shallow valleys that would lead to an excessively high proportion of intermediate particle size particles, thereby weakening the filling synergy between multi-level particles.
[0095] Furthermore, the particle size Q corresponding to q satisfies: 0.2μm≤Q≤1.0μm, that is, the particle size Q corresponding to the valley q between the second and third peaks is 0.2μm-1.0μm. Specifically, Q can be 0.2μm, 0.4μm, 0.6μm, 0.8μm, 1.0μm, or any value between any two of the above values.
[0096] By controlling Q within the above range, the transitional particle size can fill the pores between large particles without weakening the compact packing effect of the multi-stage compound due to excessive particle size.
[0097] The preparation method for large particles is the same as that for small particles, except that ferric phosphate (Fe / P ratio of 0.950⁻¹, specific surface area of 8 m²) is used. 2 / g -10 m 2 / g) is used as the initial raw material. The method for controlling large particles is the same.
[0098] In one specific embodiment, the particle size distribution curve also includes a fourth peak corresponding to the ultra-large particles. In the fourth peak, the particle size D corresponding to the peak value satisfies: 7μm < C ≤ 25μm. Specifically, D can be 7μm, 8μm, 10μm, 15μm, 20μm, 25μm, or any value between any two of the above values.
[0099] Introducing ultra-large particles can further improve the gradation effect and the structural stability of the cathode material. Specifically, ultra-large particles can participate in the packing as "skeleton particles," allowing larger and smaller particles to be more embedded in the gaps between ultra-large particles, while ultra-small particles further fill the gaps between larger and smaller particles, thereby reducing the interparticle porosity and increasing the compaction density. By limiting D to 7-25μm, it is possible to avoid the loss of macroscopic gap-filling effect due to excessively small particles, while also avoiding the problems of difficult slurry dispersion, decreased coating uniformity, and localized stress concentration on the electrode due to excessively large particles.
[0100] Furthermore, the particle size range of the ultra-large particles is 4μm-35μm. By limiting the particle size of the ultra-large particles to this range, it is possible to ensure that the size of the ultra-large particles is appropriate, which is conducive to the formation of a suitable main framework and matching with ultra-small particles, small particles, and large particles.
[0101] In this application, the ultrasmall particles can be prepared by the following method:
[0102] (1) The lithium source, iron source, phosphorus source and solvent (when containing doped metal, the solvent also includes dopant) are mixed in proportion to obtain mixed slurry 1;
[0103] (2) The mixed slurry 1 is hydrothermally reacted at 150℃-250℃ for 6h-12h to obtain lithium iron phosphate powder;
[0104] (3) Lithium iron phosphate powder and solvent (when containing a coating layer, the solvent also includes a carbon source) are mixed in a certain proportion and then ground to obtain an ultra-small particle slurry with a D50 of 100nm-300nm.
[0105] (4) The ultrafine particle slurry is spray-dried, with the inlet air temperature controlled at 180℃-220℃ and the feed rate at 25 m. 3 / h-70m 3 / h, with an outlet air temperature of 80℃-100℃, after the solvent is evaporated, ultra-small particle raw material is obtained;
[0106] (5) The ultra-small particle raw material is sintered at high temperature in an inert atmosphere or a reducing atmosphere. The sintering temperature is 650℃-750℃ and the holding time is 6h-12h to obtain ultra-small particle sintered material.
[0107] (6) The ultra-small sintered material is subjected to air jet milling with a milling pressure of 300 MPa - 500 MPa, a grading frequency of 40 Hz - 60 Hz, and a feeding rate of 1.5 tons / h - 2.5 tons / h to obtain ultra-small particles.
[0108] Small particles can be prepared by the following methods:
[0109] (1) Ferric phosphate (Fe / P = 0.960-1, specific surface area = 7 m²) 2 / g -8 m 2 The mixture of slurry 2 is prepared by mixing and dispersing the following components in proportion: (g), lithium source, and solvent (when the slurry contains a coating layer and / or doped metal, the solvent also includes a carbon source and / or dopant).
[0110] (2) The mixed slurry 2 was subjected to sand milling to obtain small particle slurry with D50 of 200nm-500nm;
[0111] (3) Spray dry the small particle slurry with an inlet air temperature of 180℃-220℃ and a feed rate of 25 m. 3 / h -70m 3 / h, with an outlet air temperature of 80℃-100℃, after the solvent is evaporated, small-particle raw materials with a D50 of 20μm-60μm are obtained;
[0112] (4) The small granular raw materials are sintered at high temperature in an inert or reducing atmosphere. The sintering temperature is 700℃-820℃ and the holding time is 6h-12h to obtain small granular sintered material.
[0113] (5) The small sintered material is subjected to air jet milling with a milling pressure of 300 MPa - 500 MPa, a grading frequency of 40 Hz - 60 Hz, and a feeding rate of 1.5 tons / h - 2.5 tons / h to obtain small particles.
[0114] The preparation method for large particles is the same as that for small particles, except that ferric phosphate (Fe / P ratio of 0.950⁻¹, specific surface area of 8 m²) is used. 2 / g -10 m 2 / g) as the initial raw material.
[0115] Ultra-large particles can be prepared by the following methods:
[0116] (1) Ferric phosphate (Fe / P = 0.960-1, specific surface area = 10 m²) 2 / g -12 m 2 / g) Lithium source and solvent (when containing a coating layer and / or doped metal, the solvent also includes a carbon source and / or dopant) are mixed and dispersed in proportion to obtain mixed slurry 4;
[0117] (2) The mixed slurry 4 was subjected to sand milling to obtain ultra-large particle slurry with D50 of 100nm-400nm;
[0118] (3) The ultra-large particle slurry is spray-dried using a two-fluid or multi-fluid spray system, with an inlet air temperature of 180℃-220℃ and a feed rate of 25 m. 3 / h -70m 3 / h, with an outlet air temperature of 80℃-100℃, after the solvent is evaporated, ultra-large raw material particles with a D50 of 4μm-40μm are obtained;
[0119] (4) The ultra-large raw material is sintered at high temperature in an inert or reducing atmosphere at a temperature of 700℃-820℃ and a holding time of 6h-12h to obtain ultra-large sintered material.
[0120] (5) Vibrate and screen the small sintered material. The vibrating screen has a mesh size of 50-500 mesh to remove the caking material and obtain ultra-large particles.
[0121] In the above, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, lithium nitrate, and lithium acetate; the iron source includes one or more of ferrous oxalate, ferric phosphate, ferric nitrate, ferrous sulfate, ferric oxide, and magnetite; the phosphorus source includes one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, ferric phosphate, and lithium dihydrogen phosphate; the carbon source includes one or more of glucose, sucrose, citric acid, polyvinyl alcohol, polyethylene glycol, and starch; the dopant includes one or more of Ti, V, Mn, Na, Cr, Mg, Co, Al, Zr, Nb, and Ni compounds, with a doping content of 300 ppm to 30,000 ppm; and the solvent includes one or more of water, ethanol, and isopropanol.
[0122] The inert gas used in an inert atmosphere includes, but is not limited to, at least one of helium, neon, argon, and krypton; the reducing gas used in a reducing atmosphere includes, but is not limited to, at least one of hydrogen and carbon monoxide.
[0123] In this application, nitrile compounds are not limited. By way of example, nitrile compounds include at least one of acetonitrile, propionitrile, butadionitrile, glutaronitrile, adiponitrile, benzonitrile, phthalonitrile, and 1,3,6-hexanetrionitrile, preferably including at least one of acetonitrile, butadionitrile, and 1,3,6-hexanetrionitrile.
[0124] It is easy to understand that the electrolyte also includes an electrolyte lithium salt and an electrolyte solvent. This application does not limit the specific type and content of the lithium salt and solvent. For example, the lithium salt can be selected from at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI). The mass content of the lithium salt can be 5%-20%. Specifically, the mass content of lithium can be 5%, 8%, 10%, 12%, 15%, 18%, 20%, and any value between any two of the above values.
[0125] The electrolyte solvent may be selected from at least one of ethylene carbonate, propylene carbonate, butene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, methyl ethyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, sulfolane, and γ-butyrolactone.
[0126] This application does not specifically limit the preparation method of the electrolyte. Exemplarily, it may include the following steps: mixing EC, EMC and DEC in a volume ratio of 1:1:1 to obtain an organic solvent, then dissolving fully dried lithium salt LiPF6 in the mixed organic solvent, and adding additives to prepare the electrolyte.
[0127] In some specific embodiments, the lithium iron phosphate (LFP) surface includes a carbon coating layer. This carbon coating layer on the surface of the LFP particles serves to form a continuous interfacial protective film between the active particles and the external environment and electrolyte. This carbon layer can be formed by vapor deposition, solution impregnation pyrolysis, or carbonization with an organic carbon source. Its function is twofold: firstly, to reduce the directly exposed surface area of the LFP, thereby reducing water absorption and side reaction sites; and secondly, to improve the interparticle electronic conductivity and enhance the continuity of the conductive network in the cathode material.
[0128] In a further embodiment, the thickness of the carbon coating layer is 0.5 nm to 120 nm. Specifically, the thickness of the carbon coating layer can be 0.5 nm, 10 nm, 30 nm, 50 nm, 80 nm, 100 nm, 120 nm, or any value between any two of the above. Controlling the thickness of the carbon coating layer within the above range can ensure a good protective effect while avoiding excessive compression of the space of the active material by the carbon coating layer, thereby achieving a better compaction density.
[0129] It should be noted that the thickness of the carbon coating layer can be controlled within the above-mentioned range by adjusting the amount of carbon source (such as glucose, polyvinyl alcohol, etc.) and the high-temperature sintering temperature.
[0130] It should also be noted that the carbon coating layer here may include at least one of a first carbon coating layer located on at least a portion of the surface of the ultrasmall particles, a second carbon coating layer located on at least a portion of the surface of the small particles, a third carbon coating layer located on at least a portion of the surface of the large particles, and a fourth carbon coating layer located on at least a portion of the surface of the ultralarge particles. The thickness of the first carbon coating layer, the second carbon coating layer, the third carbon coating layer, and the fourth carbon coating layer may all be 0.5 nm to 120 nm.
[0131] The thickness of the carbon coating layer can be tested by the following method: Discharge the battery to 2.5V at 0.33C, disassemble the lithium-ion battery to obtain the positive electrode sheet, soak the positive electrode sheet in DMC (dimethyl carbonate) at room temperature for 4 hours, take it out, dry it at room temperature with humidity ≤15%, scrape off the positive electrode active material layer on the surface of the current collector, calcine it at 400℃ for 3 hours, and obtain the positive electrode material powder after washing and drying.
[0132] Take 1 mg of the scraped active material powder and place it in a sample tube. Add anhydrous ethanol and sonicate for 40 min. Use a pipette to take a small amount of solution and drop it onto a copper grid. Finally, dry the sample completely in a vacuum drying oven. Place the sample on the test stage and transfer it to the chamber. Use TEM to measure the thickness of the coating layer at a suitable high magnification for different coating layer thicknesses. Select 5 regions for measurement and take the average value to obtain the thickness of the carbon coating layer.
[0133] In some specific embodiments, the specific surface area of the cathode material is 5-40 m². 2 / g. Specifically, the specific surface area of the cathode material can be 5 m² / g. 2 / g、10 m 2 / g、15 m 2 / g、20 m 2 / g、30 m 2 / g、40 m 2 / g and any value between any two of the above values. Controlling the specific surface area of the cathode material within the above range is beneficial for reducing surface water adsorption, while optimizing its electrochemical performance, making the insertion and extraction of lithium ions within the material smoother.
[0134] The specific surface area of the positive electrode material can be obtained by the following method: Discharge the battery to 2.5V at 0.33C, disassemble the lithium-ion battery to obtain the positive electrode sheet, soak the positive electrode sheet in DMC (dimethyl carbonate) at room temperature for 4 hours, take it out, dry it at room temperature with humidity ≤15%, scrape off the positive electrode active material layer on the surface of the current collector, calcine it at 400℃ for 3 hours, wash and dry it to obtain the positive electrode material powder, and then test it.
[0135] Specifically, at 25℃, the BET test was conducted using a nitrogen adsorption analyzer, referring to the test method in the national standard GB / T24533-2019. In an environment of 25℃ and 60% humidity, the weight of an empty small test tube was measured. 5g of the positive electrode material powder sample was placed into the sample tube. The degassing station was turned on, and the small test tube was placed in the degassing station at 200℃ for vacuum heating for 120 minutes. Nitrogen was then backfilled, and the sample tube was removed and weighed to calculate the sample mass. A multi-point BET test method was selected, with the P / P0 range set to 0.05~0.3 for six pressure points. Mass parameters were input, and the equipment automatically analyzed and read the test results.
[0136] In some specific embodiments, the porosity of the positive electrode is 10%-40%. Specifically, the porosity of the positive electrode is 10%, 20%, 30%, 40%, or any value between any two of the above. Controlling the porosity of the positive electrode within the above range is beneficial for balancing electrolyte wetting and lithium ion transport, ensuring that the battery has sufficient ion conduction channels during high-rate charge and discharge, while maintaining the structural stability of the positive electrode.
[0137] The porosity of the positive electrode sheet can be tested using the following method: Discharge the battery to 2.5V at 0.33C, remove the empty battery, disassemble the positive electrode sheet, soak it in dimethyl carbonate (DMC) solution for 4 hours, and then air dry it. Use an electrode sheet punching machine to cut the pretreated positive electrode sheet into round sheets with a diameter of 12mm. Simultaneously, use a thickness gauge to measure the thickness of the positive electrode sheet and the current collector, respectively, as h1 and h2. Weigh them using a balance with an accuracy of 0.00001g, and record the mass as m1. According to the formula v=πr 2 Calculate the volume v of the cut positive electrode sheet (h1-h2);
[0138] Immerse the positive electrode in a sealed container with a certain volume of hexadecane for 1 hour (the volume of hexadecane in the sealed solution is not required, but the amount required must be sufficient to completely submerge the positive electrode). After 1 hour, remove the positive electrode with tweezers and place it on filter paper to absorb dry until constant weight (generally, 1 hour is sufficient to absorb dry to constant weight). Weigh it using a balance and record its mass as m2.
[0139] The porosity is calculated using the formula X / v, where X = (m2 - m1) / ρ, and ρ is the density of hexadecane, 0.7734 g / cm³. 3 .
[0140] It should be noted that the positive electrode sheet provided in this application also includes a positive current collector and a positive active layer located on at least a portion of the surface of the positive current collector, with the positive electrode material located in the positive active layer.
[0141] Preferably, the positive electrode active layer is disposed on both opposite surfaces of the positive electrode current collector, that is, the positive electrode active layer is disposed on both opposite surfaces of the positive electrode current collector.
[0142] It is easy to understand that the positive electrode active layer also includes a conductive agent and a binder. This application does not limit the specific types of conductive agents and binders. The conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber; the binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinylpyrrolidone, and polyurethane.
[0143] This application does not specifically limit the preparation method of the positive electrode sheet. Exemplarily, it may include the following steps: mixing lithium iron phosphate, conductive agent, binder, and dispersant, adding N-methylpyrrolidone (NMP) solvent, and stirring under vacuum until the system is homogeneous to obtain a positive electrode slurry; uniformly coating the positive electrode slurry onto the surface of the positive electrode current collector, air-drying at room temperature, transferring to an oven for further drying, and then cold-pressing and slitting to obtain the positive electrode sheet. The mass ratio of lithium iron phosphate, conductive agent, binder, and dispersant is (94.5-98.5):(0.5-1.5):(1.3-2.2):(0.05-2).
[0144] It should be noted that this application does not limit the specific type of the positive current collector, which can be selected from at least one of aluminum foil and nickel foil.
[0145] It is also understood that the battery further includes a negative electrode sheet, which includes a negative electrode current collector and a negative electrode active layer located on at least a portion of the surface of the negative electrode current collector, preferably disposed on opposite sides of the negative electrode current collector.
[0146] In some specific embodiments, the negative electrode active layer includes a negative electrode active material, which includes at least one of graphite and silicon-based materials.
[0147] It is also understood that the negative electrode active layer includes a negative electrode binder and a negative electrode conductive agent. This application does not impose special requirements on the negative electrode current collector, negative electrode binder, and negative electrode conductive agent. For example, the negative electrode current collector is selected from at least one of copper foil, nickel foam, and copper foam. The negative electrode conductive agent may be selected from at least one of carbon black, acetylene black, Ketjen black, carbon fiber, and graphene; the negative electrode binder may be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate.
[0148] This application does not specifically limit the preparation method of the negative electrode sheet. Exemplarily, it may include the following steps: mixing negative electrode active material, conductive agent and binder, adding solvent to obtain negative electrode slurry, wherein the mass ratio of negative electrode active material: conductive agent: binder is (90-99):(0.5-3):(0.5-3), coating the negative electrode slurry on at least one surface of the negative electrode current collector, drying, rolling and cutting to obtain the negative electrode sheet.
[0149] It is also understood that the battery includes a separator. This application does not limit the specific type of separator, which can be a separator material commonly used in lithium-ion batteries, such as at least one of polypropylene separator (PP), polyethylene separator (PE), polypropylene / polyethylene bilayer composite membrane (PP / PE), polyimide electrospun separator (PI), polypropylene / polyethylene / polypropylene trilayer composite membrane (PP / PE / PP), cellulose nonwoven separator, and separator with ceramic coating.
[0150] This application also provides an electrical device, including the aforementioned positive electrode or the aforementioned battery. For the same reason, this electrical device has a long battery life and good safety performance.
[0151] The electrical equipment in this application may include, but is not limited to, electric vehicles (such as pure electric vehicles, hybrid electric vehicles, and electric bicycles), consumer electronic devices (such as smartphones, laptops, and wearable devices), energy storage devices (such as home energy storage cabinets, industrial energy storage systems, and photovoltaic energy storage power stations), and power tools (such as electric drills, electric wrenches, and electric saws).
[0152] The technical solution of this application will be further explained below with reference to specific embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or as recommended by the manufacturer. Unless otherwise specified, all reagents used are commercially available or obtained through public channels.
[0153] Example 1
[0154] This embodiment provides a battery, which is prepared through the following steps:
[0155] Step 1, Preparation of the positive electrode sheet;
[0156] The positive electrode sheet in this embodiment is prepared through the following steps:
[0157] 1) Preparation of ultrafine particles: Lithium hydroxide (lithium source), ferrous sulfate (FeSO4·7H2O) (iron source), phosphoric acid (phosphoric acid source), and dopants (specifically titanium dioxide and vanadium pentoxide) were mixed with deionized water at a stoichiometric ratio of Li:Fe:P = 1:1:1, with titanium dioxide and vanadium pentoxide accounting for 0.40% and 0.15% of the iron source mass, respectively, to obtain mixed slurry 1. Mixed slurry 1 was hydrothermally reacted at 150℃ for 6 hours to obtain lithium iron phosphate powder. The lithium iron phosphate powder was mixed with a carbon source (specifically polyethylene glycol and sucrose at a mass ratio of 4:5) at a mass ratio of 1:0.09 with deionized water and ground to obtain an ultrafine particle slurry (D50 particle size of 105 nm). The ultrafine particle slurry was spray-dried at an inlet air temperature of 180℃ and a feed rate of 50 m / s. 3 The feed rate is 45 Hz (with a feed rate of 2 tons / h at 50 Hz), the pulverizing pressure is 400 MPa, and the grading frequency is 55 Hz to obtain ultra-small raw materials. The ultra-small raw materials are then subjected to high-temperature sintering treatment at 700 ℃ for 8 hours in a nitrogen atmosphere to obtain ultra-small sintered materials. Subsequently, the ultra-small sintered materials are subjected to airflow pulverization treatment at a feed rate of 45 Hz (with a feed rate of 2 tons / h at 50 Hz), a pulverizing air pressure of 400 MPa, and a grading frequency of 55 Hz to obtain ultra-small particles.
[0158] 2) Preparation of small particles: Ferric phosphate (Fe / P ratio 0.975, specific surface area 7.5 m²) was prepared. 2 A mixture of lithium carbonate (g), polyethylene glycol (CG), sucrose (CG), titanium dioxide (DO), and vanadium pentoxide (DO) was prepared and dispersed with deionized water in a mass ratio of 100:25.25:4.20:5.15:0.40:0.15 to obtain a mixed slurry 2. The mixed slurry 2 was then milled to obtain small particle slurry (D50 particle size of 380 nm). The small particle slurry was then spray-dried at an inlet air temperature of 180℃ and a feed rate of 35 m / s. 3 / h, outlet air temperature 100℃, to obtain small granular raw material; the small granular raw material is subjected to high-temperature sintering treatment, specifically nitrogen atmosphere, constant temperature sintering treatment at 795℃ for 8h, to obtain small granular sintered material; the small granular sintered material is subjected to crushing and deagglomeration treatment, feeding frequency 50Hz (feeding amount is 2 tons / h), crushing air pressure 450Mpa, grading frequency 50Hz, to obtain small particles.
[0159] 3) Preparation of large particles: Ferric phosphate (Fe / P ratio 0.966, specific surface area 9.0 m²) was prepared. 2 A mixture of lithium carbonate ( / g), polyethylene glycol (carbon source), sucrose (carbon source), titanium dioxide (dopant), and vanadium pentoxide (dopant) was prepared and dispersed with deionized water in a mass ratio of 100:25.25:4.20:5.15:0.40:0.15. The mixture was then milled to obtain large-particle slurry (D50 particle size 462nm). The large-particle slurry was then spray-dried at an inlet air temperature of 180℃ and a feed rate of 45m / s. 3 / h, with an outlet air temperature of 100℃, large raw material particles are obtained; the large raw material particles are subjected to high-temperature sintering treatment, specifically in a nitrogen atmosphere, at a constant temperature of 810℃ for 8h, to obtain large sintered material particles; the large sintered material particles are then subjected to crushing and deagglomeration treatment, with a feeding frequency of 60Hz (of which, the feeding amount at 50Hz is 2 tons / h), a crushing air pressure of 500Mpa, and a grading frequency of 45Hz, to obtain large particles.
[0160] 4) Preparation of ultra-large particles: Ferric phosphate (Fe / P ratio 0.956, specific surface area 11.0 m²) was used. 2 Lithium carbonate (lithium source), polyethylene glycol (carbon source), sucrose (carbon source), titanium dioxide (dopant), and vanadium pentoxide (dopant) were mixed and dispersed with deionized water in a mass ratio of 100:25.25:4.20:5.15:0.40:0.15 to obtain mixed slurry 4. Mixed slurry 4 was then milled to obtain ultra-large particle slurry (D50 particle size of 300 nm). The ultra-large particle slurry was then subjected to two-fluid spray drying at an inlet air temperature of 180℃ and a feed rate of 30 m / s. 3 / h, with an outlet air temperature of 100℃, ultra-large raw material particles are obtained; the ultra-large raw material particles are subjected to high-temperature sintering treatment, specifically in a nitrogen atmosphere, at a constant temperature of 820℃ for 8 hours, to obtain ultra-large sintered material particles; the ultra-large sintered material particles are subjected to vibratory sieving (200 mesh screen) to obtain ultra-large particles.
[0161] 5) The above-mentioned ultra-small particles, small particles, large particles and ultra-large particles are mechanically mixed in a mass ratio of 6:67:20:7 to obtain lithium iron phosphate material.
[0162] 6) The above-mentioned lithium iron phosphate material, binder PVDF, and conductive agent SP are dispersed in NMP at a mass ratio of 97.9:1.6:0.5 to obtain a positive electrode slurry. The positive electrode slurry is coated on aluminum foil to obtain a double-sided coated positive electrode sheet. Then, it is rolled and cut to obtain a positive electrode sheet.
[0163] Step 2, preparation of the negative electrode sheet;
[0164] The negative electrode active material graphite, binder CMC, and conductive agent SP were dispersed in deionized water at a mass ratio of 96.4:0.6:0.6 to obtain a negative electrode slurry. The negative electrode slurry was coated onto copper foil to obtain a double-sided coated electrode sheet, which was then rolled and cut to obtain the negative electrode sheet. The areal density of the negative electrode sheet on one side was 104 g / m³. 2 The compacted density is 1.60 g / cm³. 3 .
[0165] Step 3, preparation of electrolyte;
[0166] Ethylene carbonate (EC) and diethyl carbonate (DEC) were mixed at a volume ratio of 2:1 to obtain an organic solvent. Then, a nitrile compound (specifically acetonitrile) and fully dried lithium salt LiPF6 were dissolved in the mixed organic solvent to prepare an electrolyte with a lithium salt LiPF6 concentration of 1 mol / L and a nitrile compound mass content of 10%.
[0167] Step 4, battery assembly;
[0168] The positive electrode sheet from step 1, the separator (specifically a polyethylene separator coated with ceramic layers on both sides, the ceramic layers including 83% boehmite and 17% PVDF binder by mass) and the negative electrode sheet from step 2 are wound in sequence to obtain a bare cell. The bare cell is placed in an outer packaging shell, dried, and then injected with the electrolyte from step 3. After vacuum sealing, settling, formation, and shaping processes, a 72mm×173mm×203mm lithium-ion battery is obtained.
[0169] Example 2
[0170] This embodiment provides a battery whose preparation method differs from that of Embodiment 1 in that...
[0171] In step 1, the ultra-small particle sintering material is crushed at a feeding frequency of 45 Hz, a crushing pressure of 400 MPa, and a grading frequency of 60 Hz.
[0172] In step 1, 2), the small particle sinter is crushed and deagglomerated, with a feeding frequency of 50 Hz, a crushing air pressure of 400 MPa, and a classification frequency of 60 Hz.
[0173] In step 1, section 4), the sintering temperature of the ultra-large raw material is 700℃ and the sintering time is 7h.
[0174] In step 1, 5), ultra-small particles, small particles, large particles, and ultra-large particles are mixed in a mass ratio of 8:70:17:5 to obtain lithium iron phosphate material.
[0175] In step 3, the nitrile compound is succinic anionyl nitrile, and its mass content is 20%.
[0176] Example 3
[0177] This embodiment provides a battery whose preparation method differs from that of Embodiment 1 in that...
[0178] In step 1, 1), the high-temperature sintering treatment temperature of the ultra-small particle raw material is 730℃ and the time is 8h. The ultra-small particle sintering material is crushed with a feeding frequency of 40Hz, a crushing air pressure of 400Mpa, and a classification frequency of 60Hz.
[0179] In step 1, 2), the small particle sinter is crushed and deagglomerated, with a feeding frequency of 40 Hz, a crushing air pressure of 400 MPa, and a classification frequency of 60 Hz.
[0180] In step 1, section 4), the sintering temperature of the ultra-large raw material is 820℃ and the sintering time is 11h.
[0181] In step 1, 5), ultra-small particles, small particles, large particles, and ultra-large particles are mixed in a mass ratio of 10:70:13:7 to obtain lithium iron phosphate material.
[0182] In step 3, the nitrile compound is adiponitrile, with a mass content of 30%.
[0183] Example 4
[0184] This embodiment provides a battery whose preparation method differs from that of Embodiment 1 in that...
[0185] In step 1, 1), the high-temperature sintering treatment temperature of the ultra-small particle raw material is 730℃ and the time is 8h. The ultra-small particle sintering material is crushed with a feeding frequency of 40Hz, a crushing air pressure of 500Mpa, and a grading frequency of 60Hz.
[0186] In step 1, 2), the small particle sinter is crushed and deagglomerated, with a feeding frequency of 40 Hz, a crushing air pressure of 500 MPa, and a classification frequency of 50 Hz.
[0187] In step 1, 3), the large particle sinter is crushed and deagglomerated, with a feeding frequency of 55 Hz, a crushing air pressure of 500 MPa, and a classification frequency of 60 Hz.
[0188] In step 1, 5), ultra-small particles, small particles, large particles, and ultra-large particles are mixed in a mass ratio of 7:67:20:6 to obtain lithium iron phosphate material.
[0189] In step 3, the mass content of nitrile compounds is 30%.
[0190] Example 5
[0191] This embodiment provides a battery whose preparation method differs from that of Embodiment 1 in that...
[0192] In step 1, 1), the high-temperature sintering treatment of ultra-small particle raw material is 650℃ for 12 hours. The ultra-small particle sintering material is crushed with a feeding frequency of 50Hz, a crushing air pressure of 300Mpa, and a grading frequency of 55Hz.
[0193] In step 1, 2), the sintering temperature of the small particle raw material is 810℃ and the time is 8h; the small particle sintering material is crushed and deagglomerated, the feeding frequency is 50Hz, the crushing pressure is 400Mpa, and the grading frequency is 60Hz.
[0194] In step 1, 3), the large particle sinter is crushed and deagglomerated, with a feeding frequency of 60Hz, a crushing air pressure of 350Mpa, and a classification frequency of 40Hz.
[0195] In step 1, 5), ultra-small particles, small particles, large particles, and ultra-large particles are mixed in a mass ratio of 11:70:13:6 to obtain lithium iron phosphate material.
[0196] In step 3, the mass content of nitrile compounds is 9.5%.
[0197] Example 6
[0198] This embodiment provides a battery whose preparation method differs from that of Embodiment 1 in that...
[0199] In step 1, 1), the high-temperature sintering treatment of ultra-small particle raw material is 680℃ for 11h. The ultra-small particle sintering material is crushed with a feeding frequency of 40Hz, a crushing pressure of 430MPa, and a grading frequency of 55Hz.
[0200] In step 1, 2), the sintering temperature of the small-particle raw material is 820℃ and the time is 9h; the small-particle sintered material is crushed and deagglomerated, with a feeding frequency of 50Hz, a crushing pressure of 500Mpa, and a classification frequency of 40Hz.
[0201] In step 1, 5), ultra-small particles, small particles, large particles, and ultra-large particles are mixed in a mass ratio of 7:67:20:6 to obtain lithium iron phosphate material.
[0202] In step 3, the mass content of nitrile compounds is 10%.
[0203] Example 7
[0204] This embodiment provides a battery whose preparation method differs from that of Embodiment 1 in that...
[0205] In step 1, the ultra-small particle sintering material is crushed at a feeding frequency of 45 Hz, a crushing pressure of 400 MPa, and a grading frequency of 40 Hz.
[0206] In step 1, 2), the small particle sinter is crushed and deagglomerated, with a feeding frequency of 50 Hz, a crushing air pressure of 500 MPa, and a classification frequency of 55 Hz.
[0207] In step 1, 5), ultra-small particles, small particles, large particles, and ultra-large particles are mixed in a mass ratio of 8:70:17:5 to obtain lithium iron phosphate material.
[0208] In step 3, the mass content of nitrile compounds is 20%.
[0209] Example 8
[0210] This embodiment provides a battery whose preparation method differs from that of Embodiment 1 in that...
[0211] In step 1, 1), the high-temperature sintering treatment of ultra-small particle raw material is 680℃ for 11h. The ultra-small particle sintering material is crushed with a feeding frequency of 40Hz, a crushing air pressure of 500Mpa, and a grading frequency of 60Hz.
[0212] In step 1, 2), the small particle sinter is crushed and deagglomerated, with a feeding frequency of 45 Hz, a crushing air pressure of 500 MPa, and a classification frequency of 40 Hz.
[0213] In step 1, 5), ultra-small particles, small particles, large particles, and ultra-large particles are mixed in a mass ratio of 4:67:20:9 to obtain lithium iron phosphate material.
[0214] In step 3, the mass content of nitrile compounds is 50%.
[0215] Example 9
[0216] This embodiment provides a battery whose preparation method differs from that of Embodiment 1 in that...
[0217] In step 1, 1), the high-temperature sintering treatment of ultra-small particle raw material is 750℃ for 6 hours. The ultra-small particle sintering material is crushed with a feeding frequency of 40Hz, a crushing pressure of 500Mpa, and a grading frequency of 60Hz.
[0218] In step 1, 2), the small particle sinter is crushed and deagglomerated, with a feeding frequency of 50 Hz, a crushing air pressure of 500 MPa, and a classification frequency of 60 Hz.
[0219] In step 1, 5), ultra-small particles, small particles, large particles, and ultra-large particles are mixed in a mass ratio of 18:61:16:5 to obtain lithium iron phosphate material.
[0220] The mass content of nitrile compounds in step 3 is 5.4%.
[0221] Example 10
[0222] This embodiment provides a battery whose preparation method differs from that of Embodiment 1 in that...
[0223] In step 1, the small sintered material is crushed at a feeding frequency of 40 Hz, a crushing pressure of 500 MPa, and a grading frequency of 60 Hz.
[0224] In step 1, 2), the small particle sinter is crushed and deagglomerated, with a feeding frequency of 45 Hz, a crushing air pressure of 450 MPa, and a classification frequency of 45 Hz.
[0225] In step 1, 5), ultra-small particles, small particles, large particles, and ultra-large particles are mixed in a mass ratio of 19:61:15:5 to obtain lithium iron phosphate material.
[0226] The mass content of nitrile compounds in step 3 is 5%.
[0227] Example 11
[0228] This embodiment provides a battery whose preparation method differs from that of Embodiment 1 in that...
[0229] In step 1, the ultra-small particle sintering material is crushed at a feeding frequency of 45 Hz, a crushing pressure of 400 MPa, and a grading frequency of 50 Hz.
[0230] In step 1, 2), the small particle sinter is crushed and deagglomerated, with a feeding frequency of 50 Hz, a crushing air pressure of 450 MPa, and a classification frequency of 50 Hz.
[0231] In step 1, 5), ultra-small particles, small particles, large particles, and ultra-large particles are mixed in a mass ratio of 8:67:18:7 to obtain lithium iron phosphate material.
[0232] The mass content of nitrile compounds in step 3 is 5%.
[0233] Example 12
[0234] This embodiment provides a battery whose preparation method differs from that of Embodiment 1 in that...
[0235] In step 1, the ultra-small particle sintering material is crushed at a feeding frequency of 45 Hz, a crushing pressure of 400 MPa, and a grading frequency of 50 Hz.
[0236] In step 1, 2), the small particle sinter is crushed and deagglomerated, with a feeding frequency of 50 Hz, a crushing air pressure of 450 MPa, and a classification frequency of 50 Hz.
[0237] In step 1, 5), ultra-small particles, small particles, large particles, and ultra-large particles are mixed in a mass ratio of 17:60:13:10 to obtain lithium iron phosphate material.
[0238] The mass content of nitrile compounds in step 3 is 5%.
[0239] Example 13
[0240] This embodiment provides a battery whose preparation method differs from that of Embodiment 1 in that...
[0241] In step 1, the ultra-small particle sintering material is crushed at a feeding frequency of 50 Hz, a crushing pressure of 450 MPa, and a grading frequency of 50 Hz.
[0242] In step 1, 2), the sintering temperature of the small particle raw material is 750℃ and the time is 12h; the small particle sintering material is crushed and deagglomerated, with a feeding frequency of 40Hz, a crushing air pressure of 500Mpa, and a classification frequency of 60Hz.
[0243] In step 1, 5), ultra-small particles, small particles, large particles, and ultra-large particles are mixed in a mass ratio of 8:70:17:5 to obtain lithium iron phosphate material.
[0244] In step 3, the mass content of nitrile compounds is 15%.
[0245] Example 14
[0246] This embodiment provides a battery whose preparation method differs from that of Embodiment 1 in that it does not contain ultra-large particles; and in step 1), the high-temperature sintering treatment of ultra-small particle raw materials is carried out at a temperature of 710°C for 6 hours.
[0247] In step 1, section 2), the high-temperature sintering treatment of the small-particle raw materials is carried out at a temperature of 800℃ for 8 hours.
[0248] In step 1, 3), the large particle sinter is crushed and deagglomerated, with a feeding frequency of 40 Hz, a crushing air pressure of 500 MPa, and a classification frequency of 50 Hz.
[0249] In step 1, 5), ultra-small particles, small particles, and large particles are mixed in a mass ratio of 7:70:23 to obtain lithium iron phosphate material.
[0250] In step 3, the mass content of nitrile compounds is 10%.
[0251] Example 15
[0252] This embodiment provides a battery whose preparation method differs from that of Embodiment 1 in that it does not contain ultra-large particles; and in step 1), the ultra-small particle sintering material is pulverized, with a feeding frequency of 40Hz, a pulverizing pressure of 400Mpa, and a grading frequency of 60Hz.
[0253] In step 1, 5), ultra-small particles, small particles, and large particles are mixed in a mass ratio of 8:68:24 to obtain lithium iron phosphate material.
[0254] The mass content of nitrile compounds in step 3 is 33%.
[0255] Example 16
[0256] This embodiment provides a battery whose preparation method differs from that of Embodiment 1 in that it does not contain ultra-large particles; and in step 1), the ultra-small particle sintering material is pulverized, with a feeding frequency of 40Hz, a pulverizing pressure of 400Mpa, and a grading frequency of 55Hz.
[0257] In step 1, 3), the large particle sinter is crushed and deagglomerated, with a feeding frequency of 60 Hz, a crushing air pressure of 500 MPa, and a classification frequency of 50 Hz.
[0258] In step 1, 5), ultra-small particles, small particles, and large particles are mixed in a mass ratio of 10.5:70:19.5 to obtain lithium iron phosphate material.
[0259] In step 3, the mass content of nitrile compounds is 10%.
[0260] Example 17
[0261] This embodiment provides a battery whose preparation method differs from that of Embodiment 1 in that it does not contain ultra-large particles; and in step 1), the ultra-small particle raw material is subjected to high-temperature sintering treatment at a temperature of 720°C for 7 hours, and the ultra-small particle sintering material is crushed with a feeding frequency of 50Hz, a crushing pressure of 500MPa, and a grading frequency of 60Hz.
[0262] In step 1, 2), the high-temperature sintering treatment of small particle raw materials is 810℃ for 8 hours. The small particle sintering material is crushed and deagglomerated. The feeding frequency is 45Hz, the crushing pressure is 400Mpa, and the grading frequency is 60Hz.
[0263] In step 1, 5), ultra-small particles, small particles, and large particles are mixed in a mass ratio of 4:68:28 to obtain lithium iron phosphate material.
[0264] In step 3, the mass content of nitrile compounds is 50%.
[0265] Example 18
[0266] This embodiment provides a battery whose preparation method differs from that of Embodiment 1 in that it does not contain ultra-large particles; and in step 1), the ultra-small particle sintering material is pulverized, with a feeding frequency of 40Hz, a pulverizing pressure of 500Mpa, and a grading frequency of 50Hz.
[0267] In step 1, 2), the small particle sinter is crushed and deagglomerated, with a feeding frequency of 40 Hz, a crushing air pressure of 500 MPa, and a classification frequency of 60 Hz.
[0268] In step 1, 5), ultra-small particles, small particles, and large particles are mixed in a mass ratio of 19:70:21 to obtain lithium iron phosphate material.
[0269] The mass content of nitrile compounds in step 3 is 5%.
[0270] Example 19
[0271] This embodiment provides a battery whose preparation method differs from that of Embodiment 1 in that it does not contain ultra-large particles; and in step 1), the ultra-small particle sintering material is pulverized, with a feeding frequency of 45Hz, a pulverizing pressure of 450Mpa, and a grading frequency of 55Hz.
[0272] In step 1, 2), the small particle sinter is crushed and deagglomerated, with a feeding frequency of 40 Hz, a crushing air pressure of 450 MPa, and a classification frequency of 45 Hz.
[0273] In step 1, 5), ultra-small particles, small particles, and large particles are mixed in a mass ratio of 11:69:20 to obtain lithium iron phosphate material.
[0274] The mass content of nitrile compounds in step 3 is 8%.
[0275] Comparative Example 1
[0276] This comparative example provides a battery whose preparation method differs from that of Example 1 in that it does not contain ultra-large particles; and in step 1), the small particle sintering material is crushed, with a feeding frequency of 40Hz, a crushing pressure of 450MPa, and a grading frequency of 50Hz.
[0277] In step 1, 2), the small particle sinter is crushed and deagglomerated, with a feeding frequency of 40 Hz, a crushing air pressure of 500 MPa, and a classification frequency of 60 Hz.
[0278] In step 1, 5), ultra-small particles, small particles, large particles, and ultra-large particles are mixed in a mass ratio of 19:61:17 to obtain lithium iron phosphate material.
[0279] The mass content of nitrile compounds in step 3 is 5%.
[0280] Comparative Example 2
[0281] This comparative example provides a battery whose preparation method differs from that of Example 1 in that, in step 1), the high-temperature sintering treatment temperature of the ultra-small particle raw material is 650°C and the time is 11h, the ultra-small particle sintering material is crushed, the feeding frequency is 40Hz, the crushing pressure is 500Mpa, and the grading frequency is 60Hz.
[0282] In step 1, 2), the small particle sinter is crushed and deagglomerated, with a feeding frequency of 40 Hz, a crushing air pressure of 500 MPa, and a classification frequency of 50 Hz.
[0283] In step 1, 5), ultra-small particles, small particles, large particles, and ultra-large particles are mixed in a mass ratio of 19:61:15:5 to obtain lithium iron phosphate material.
[0284] The mass content of nitrile compounds in step 3 is 5%.
[0285] Comparative Example 3
[0286] This comparative example provides a battery whose preparation method differs from that of Example 1 in that, in step 1), the small particle sintering material is pulverized, the feeding frequency is 50Hz, the pulverizing pressure is 500Mpa, and the grading frequency is 40Hz.
[0287] In step 1, 2), the sintering temperature of the small particle raw material is 760℃ and the time is 12h; the small particle sintering material is crushed and deagglomerated, with a feeding frequency of 50Hz, a crushing pressure of 500Mpa, and a classification frequency of 45Hz.
[0288] In step 1, 5), ultra-small particles, small particles, large particles, and ultra-large particles are mixed in a mass ratio of 4:65:20:11 to obtain lithium iron phosphate material.
[0289] In step 3, the mass content of nitrile compounds is 50%.
[0290] Experimental Example 1
[0291] 1. Particle size test
[0292] The battery was discharged at 0.33C to the lower limit voltage of 2.5V. The empty battery was then removed, and the positive electrode sheet was disassembled. The positive electrode sheet was soaked in dimethyl carbonate (DMC) solution for 4 hours, then air-dried at room temperature with humidity ≤15%. The positive electrode active material layer on the current collector surface was scraped off and calcined at 400℃ for 3 hours. After washing and drying, the positive electrode material powder was obtained. A layer of conductive adhesive was first applied to the SEM sample holder, and the positive electrode material powder to be tested was adhered to the sample holder. Loose powder was blown away, and a conductive film was then deposited. The tools and sample stage were wiped with anhydrous ethanol. The sample holder with the positive electrode material powder to be tested was placed on the sample stage and observed under a scanning electron microscope (SEM). The magnification was first adjusted to 5000x and 10000x to observe the overall dispersion state of the sample. Areas with severe agglomeration were excluded before testing. The magnification was adjusted, with the first and second particles observed at 20,000x magnification, and the third and fourth particles observed at 4,000x magnification. The particle size differences between the different particles were clearly distinguished, and the SEM images were saved for subsequent statistical analysis.
[0293] Image analysis software was used to statistically analyze the SEM images. The particle size of the cathode material particles in the images was measured using the diagonal line method. Five different non-overlapping regions were selected, and one clear SEM image was taken for each region, avoiding edges and agglomerate areas to ensure that the particles in the images were independently dispersed and without significant overlap. The statistically analyzed particle size and quantity percentages were converted into a particle size-volume percentage distribution map. The conversion formula is:
[0294] Vi'=Ni×Di 3 ,
[0295] Vi = Vi' / ∑Vi'.
[0296] Where Di represents the particle size of different particles, Ni represents the proportion of particles with size Di, Vi' represents the volume weight of particles with size Di, and Vi represents the volume proportion of particles with size Di.
[0297] Generate a particle size-volume distribution map (horizontal axis: particle size, vertical axis: volume percentage) from the statistically analyzed particle sizes for parameter reading and calculation. Record the maximum value of the first peak (a), the maximum value of the second peak (b), the maximum value of the third peak (c), and the valley between the first and second peaks (m). Then, obtain n using the formula n = m / (a + b).
[0298] The particle size A corresponding to the peak value a of the first peak: Draw a perpendicular line from the peak value a of the first peak to the horizontal axis. The value corresponding to the intersection of the perpendicular line and the horizontal axis is the particle size A.
[0299] The particle size M corresponding to the peak m: Draw a perpendicular line from the peak m to the horizontal axis. The value corresponding to the intersection of the perpendicular line and the horizontal axis is the particle size M.
[0300] The particle size B corresponding to the peak value b of the second peak: Draw a perpendicular line from the peak value b of the second peak to the horizontal axis. The value corresponding to the intersection of the perpendicular line and the horizontal axis is the particle size B.
[0301] The peak intensity q between the second and third peaks: Draw a straight line perpendicular to the vertical axis from the valley between the second and third peaks, and record the intersection of the line and the vertical axis, which represents the peak intensity q.
[0302] The particle size Q corresponding to the peak intensity q: Draw a perpendicular line from the valley between the second and third peaks to the horizontal axis. The value corresponding to the intersection of the perpendicular line and the horizontal axis is Q.
[0303] 2. Test on the percentage of ultra-small particles
[0304] Five distinct non-overlapping regions were obtained using the same method as described in the particle size analysis. A clear SEM image was taken for each region, avoiding edges and agglomerated areas to ensure that the particles in the image were independently dispersed without significant overlap. Then, the cathode material particles in the target particle size range (i.e., 20nm-100nm) in each SEM image region were statistically analyzed using the same method as described in the particle size analysis. Finally, f was calculated according to the following formula.
[0305] Single-region f-value: ;
[0306] Final f-value: Take the average of the 5 regions, i.e. ;
[0307] Where, N 1i N represents the number of particles of the target region that are diagonally bounded within the i-th SEM image region; 总i Let be the total number of all particles diagonally crossed in the i-th SEM image region.
[0308] Table 1
[0309]
[0310] Experimental Example 2
[0311] The electrochemical performance of the batteries in the above embodiments and comparative examples was tested as follows, and the test results are shown in Table 2.
[0312] (1) Energy density test
[0313] The weight of the battery is measured and recorded as m. The battery is placed in a fixture, and a force of 3000N is applied. At 25°C, it is charged at a constant current of 0.33C to the upper limit voltage of 3.65V, and then left to rest for 30 minutes. The battery is then discharged at a constant current of 0.33C to the lower limit voltage of 2.5V, and left to rest for 30 minutes. This cycle is repeated for 3 times to obtain the discharge capacity (in Ah) and energy E (average value of the three cycles).
[0314] Discharge energy density = E / m (in Wh / kg).
[0315] (2) Gas production test
[0316] Battery gas generation tests were conducted using the principle of buoyancy. Specifically, the battery was emptied using a battery charging and discharging device under the following conditions: current 0.33C, cutoff voltage 2.5V. Then, it was fully charged to its final capacity under the following conditions: a) Final capacity: constant current charging at 0.33C to the upper limit voltage of 3.65V, constant voltage charging until the current is less than or equal to 0.05C, then discharging at 0.33C to the lower limit voltage of 2.5V. This constituted one cycle, with three charge-discharge cycles. The discharge capacity of the third cycle was taken as the battery capacity C0; b) Full charge: constant current charging at 0.33C to the upper limit voltage of 3.65V, constant voltage charging until the current is less than or equal to 0.05C. After full charging, the secondary battery volume was measured using the water displacement method and recorded as V0.
[0317] After storing the battery in a 60°C oven for 7 days, remove it and wait for the battery temperature to drop to room temperature. Then, use the water displacement method to test the battery volume again and record it as V1. The amount of gas produced by the battery during this storage period is the difference between V1 and V0. Divide this value by the battery's rated capacity to get the amount of gas produced by the secondary battery per ampere-hour.
[0318] The specific steps for testing the volume of a secondary battery using the water displacement method are as follows: (i) Add an appropriate amount of pure water to the container and test its density with a hydrometer and record it; (ii) Adjust the balance to be level and tare the electrolyte (tare the electrolyte before testing each battery); (iii) Submerge the battery body along with the tabs in the solution, ensuring that the secondary battery does not contact the container wall, and record the reading as T after stabilization; (iv) Turn off the balance and seal the container to prevent reagent evaporation. The formula for calculating the volume of a secondary battery is T / ρ_liquid; where, before and after storage, tests are performed to obtain T0 and T1 respectively; then the difference between V1 and V0 is: V1-V0=T1 / ρ_liquid-T0 / ρ_liquid.
[0319] Gas production at 60°C = (V1-V0) / C0.
[0320] (3) AC impedance
[0321] After removing the insulating tape from the battery under test, wipe the battery's conductive tabs with industrial alcohol (greater than 99.7% by mass) and lint-free paper to ensure the surface is clean and free of stains. Then, place the battery under test in a high-low temperature chamber with a temperature control accuracy of ±2℃. Insert the channel wires of the electrochemical workstation (Wantong M204) into the chamber through the chamber's opening, and then connect the working electrode and counter electrode of the channel wire to the corresponding tabs of the battery. Close the chamber door, adjust the temperature to the test temperature of 25℃, and allow it to reach thermal equilibrium. Edit the test parameters on the testing computer. After the test, remove the battery connected to the electrochemical workstation channel wires and insulate its conductive tabs with insulating tape. Then, export the raw data and calculate the AC impedance (EIS) on the testing computer. The test parameters were: -3V to 10V, test time 10s, AC amplitude 5mV, and frequency 10E6Hz-0.01Hz.
[0322] Table 2
[0323]
[0324] The results above show that the batteries provided in Examples 1-19 have higher energy densities than those in Comparative Examples 1-3, and lower gas production and AC impedance than those in Comparative Examples 1-3. This indicates that the positive electrode sheet provided in this application, by controlling the proportion of ultra-small particles f, combined with a bimodal particle size distribution with a first and second peak and a lower peak-valley intensity characterization value n, and further by regulating the mass content of nitrile compounds in the electrolyte to satisfy the synergistic constraint relationship of 0.35≤f / (n×d)≤103, can match the high compaction requirements of particles with the water suppression requirements of the interface. This improves the compaction density of the positive electrode sheet while suppressing the lithium salt decomposition and gas production side reactions caused by water absorption, and maintains good lithium-ion transport performance, thereby improving the energy density of the battery and reducing gas production and AC impedance.
[0325] The results above show that the batteries provided in Examples 1-7 have higher energy densities than those in Examples 8-13, and lower gas production and AC impedance than those in Examples 8-13. The batteries provided in Examples 14-16 have higher energy densities than those in Examples 17-19, and lower gas production and AC impedance than those in Examples 17-19. This indicates that the positive electrode provided in this application, when further satisfying 1.5≤f / (n×d)≤17, is beneficial to better improve the energy density of the battery and reduce gas production and AC impedance.
[0326] Finally, it should be noted that other embodiments of this application will readily conceive of by those skilled in the art upon consideration of the specification and practice of the application disclosed herein. This application is intended to cover any variations, uses, or adaptations of this application that follow the general principles of this application and include common knowledge or customary techniques in the art not disclosed herein, and is not limited to what has been described above, and various modifications and changes may be made without departing from its scope. The scope of this application is limited only by the appended claims.
Claims
1. A battery, characterized in that, It includes a positive electrode sheet and an electrolyte. The positive electrode sheet includes a positive electrode material, which includes lithium iron phosphate. The lithium iron phosphate includes ultra-small particles, small particles and large particles. The particle size range of the ultra-small particles is 20nm-100nm. Based on the total number of lithium iron phosphate particles, the proportion of the number of ultra-small particles is f. The volumetric particle size distribution curve of the cathode material includes a first peak corresponding to the ultrasmall particles, a second peak corresponding to the small particles, and a third peak corresponding to the large particles. In the first peak, the particle size A corresponding to the peak value is 30nm-90nm, and the peak intensity corresponding to the peak value is a; In the second peak, the particle size B corresponding to the peak value is 120nm-800nm, and the peak intensity corresponding to the peak value is b. The peak intensity corresponding to the valley between the first and second peaks is m; In the third peak, the particle size C corresponding to the peak value is 1μm-4μm; The electrolyte contains nitrile compounds, and the mass content of the nitrile compounds is d based on the total mass of the electrolyte; f, m, and b satisfy: 0.35 ≤ f / (n×d) ≤ 103; Where n = m / (a + b).
2. The battery according to claim 1, characterized in that, 1.5≤f / (n×d)≤17.
3. The battery according to claim 1, characterized in that, 5%≤f≤20%。 4. The battery according to any one of claims 1-3, characterized in that, 5%≤d≤50%。 5. The battery according to claim 4, characterized in that, 0.0357≤n≤0.333。 6. The battery according to claim 4, characterized in that, 0.5%<a≤6%。 7. The battery according to claim 4, characterized in that, The particle size M corresponding to m satisfies: 100nm≤M≤120nm.
8. The battery according to claim 4, characterized in that, The particle size A corresponding to a satisfies: 20nm≤|MA|≤80nm.
9. The battery according to any one of claims 1-3 and 5-8, characterized in that, In the second peak, the particle size corresponding to the peak value is B, where 100nm≤|BM|≤700nm.
10. The battery according to any one of claims 1-3 and 5-8, characterized in that, 4% ≤ b ≤ 10%; and / or, 0.5% ≤ m ≤ 2%.
11. The battery according to any one of claims 1-3 and 5-8, characterized in that, The peak intensity corresponding to the peak value of the third peak is c, and the peak intensity c corresponding to the peak value satisfies: 4%≤c≤10%.
12. The battery according to claim 11, characterized in that, The peak intensity corresponding to the valley between the second and third peaks is q, where 0.1≤q / (b+c)≤0.
5.
13. The battery according to claim 12, characterized in that, The particle size Q corresponding to q satisfies: 0.2μm≤Q≤1.0μm; And / or, the peak intensity q satisfies: 2%≤q≤8%.
14. The battery according to claim 11, characterized in that, The particle size distribution curve also includes a fourth peak corresponding to the ultra-large particles. In the fourth peak, the particle size D corresponding to the peak value satisfies: 7μm<D≤25μm; And / or, the particle size range of the ultra-large particles is 4μm-35μm.
15. The battery according to any one of claims 1-3, 5-7, and 11-14, characterized in that, The nitrile compounds include at least one selected from acetonitrile, propionitrile, butadiene nitrile, glutaronitrile, adiponitrile, benzonitrile, phthalonitrile, and 1,3,6-hexanetrionitrile.
16. The battery according to claim 15, characterized in that, The nitrile compounds include at least one of acetonitrile, succinic anionyl nitrile, and 1,3,6-hexanetrionitrile.
17. The battery according to claims 1-3, 5-8, 12-14, and 16, characterized in that, The lithium iron phosphate surface also includes a carbon coating layer; Preferably, the thickness of the carbon coating layer is 0.5 nm to 120 nm.
18. The battery according to claims 1-3, 5-8, 12-14, and 16, characterized in that, The specific surface area of the cathode material is 5 m². 2 / g -40 m 2 / g; And / or, the porosity of the positive electrode is 10%-40%.
19. The battery according to claims 1-3, 5-8, 12-14, and 16, characterized in that, The battery also includes a negative electrode sheet, and the negative electrode active layer of the negative electrode sheet includes a negative electrode active material, which includes at least one of graphite and silicon-based materials. The positive electrode sheet includes a positive current collector and a positive active layer disposed on opposite sides of the positive current collector, with the positive electrode material located in the positive active layer.
20. An electrical appliance, characterized in that, Includes the battery as described in any one of claims 1-19.
